Analisis Permintaan Uang Kartal di Indonesia - Denny Yurizon; Doni Satria (Universitas Negeri Padang, 2026)
This study is motivated by the rapid development of payment systems in Indonesia and the limited number of studies integrating digital, banking, and macroeconomic factors in explaining the demand for currency in circulation. The study aims to examine the effects of electronic money, demand deposits, time deposit interest rates, inflation, and Gross Domestic Product (GDP) on the demand for currency in circulation in Indonesia. Quarterly data for 2015–2024 obtained from Bank Indonesia and Statistics Indonesia (BPS) were analyzed using the Error Correction Model (ECM). The results show that electronic money and time deposit interest rates have no significant effect in either the short run or the long run. Demand deposits positively and significantly affect currency demand only in the long run, indicating a complementary relationship with the demand for currency in circulation. Inflation has a negative and significant long-run effect, while GDP has a positive and significant effect in both the short run and the long run. Simultaneously, all independent variables significantly affect the demand for currency in circulation. These findings indicate that the demand for currency in circulation in Indonesia remains mainly driven by real economic activity rather than by the expansion of digital payment instruments. Therefore, monetary stability should be maintained alongside the development of an efficient and inclusive digital payment ecosystem.